1999
DOI: 10.1159/000012024
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of c-<i>myc</i> in Hepatocellular Carcinoma: Correlation with Clinicopathologic Features, Proliferative Activity and p53 Overexpression

Abstract: Expression of the proto-oncogene c-myc has been implicated in liver regeneration and hepatocarcinogenesis. The biologic significance of c-myc gene amplification in human hepatocellular carcinoma, however, is unconfirmed. We correlated c-myc gene amplification with clinicopathologic features, proliferative activity, and p53 expression in 42 resected tumors. c-myc amplification in tumor tissue was determined using a differential polymerase chain reaction, a useful procedure for the evaluation of gene amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 18 publications
4
102
1
1
Order By: Relevance
“…Also, in vivo studies have shown that c-myc expression may gradually increase from normal liver to chronic hepatitis, cirrhosis and HCC (Himeno et al, 1988). Mechanisms of c-myc overexpression during human hepatocarcinogenesis are poorly understood, but might be related to amplification of the gene or hypomethylation of its regulatory sequences (Shen et al, 1998;Kawate et al, 1999). Speculation of c-myc overexpression as being an early event in the premalignant steps of human hepatocarcinogenesis may be of major importance since it has been found in more than 50% of human HCCs and their corresponding adjacent nontumor liver (Zhang et al, 1990;Kawate et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in vivo studies have shown that c-myc expression may gradually increase from normal liver to chronic hepatitis, cirrhosis and HCC (Himeno et al, 1988). Mechanisms of c-myc overexpression during human hepatocarcinogenesis are poorly understood, but might be related to amplification of the gene or hypomethylation of its regulatory sequences (Shen et al, 1998;Kawate et al, 1999). Speculation of c-myc overexpression as being an early event in the premalignant steps of human hepatocarcinogenesis may be of major importance since it has been found in more than 50% of human HCCs and their corresponding adjacent nontumor liver (Zhang et al, 1990;Kawate et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of c-myc overexpression during human hepatocarcinogenesis are poorly understood, but might be related to amplification of the gene or hypomethylation of its regulatory sequences (Shen et al, 1998;Kawate et al, 1999). Speculation of c-myc overexpression as being an early event in the premalignant steps of human hepatocarcinogenesis may be of major importance since it has been found in more than 50% of human HCCs and their corresponding adjacent nontumor liver (Zhang et al, 1990;Kawate et al, 1999). This is confirmed in several observations that have suggested that, although c-myc triggering cellular growth may play a role in the premalignant steps during the process of malignant transformation (as reflected by its high overexpression level in peritumor liver), it may not play a significant role in sustaining the growth of the tumor cells (as reflected by its lower overexpression level in the corresponding tumor tissue) (Su et al, 1985;Yuen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the observation of downregulation of Bcl-2 and overexpression of p53 in advanced human HCCs that are known to exhibit high apoptosis rates. 64,65 In these tumors, apoptosis was found in neoplastic hepatocytes positive for P53 expression and negative for the expression of Bcl-2 and proliferating cell nuclear antigen, whereas it was absent in Bcl-2 positive cells. 66 Our data suggest that these changes may occur even before the appearance of fully malignant lesions.…”
Section: Table 3 Effect Of Amph Treatment On Expression Of Apoptosismentioning
confidence: 97%
“…The multiple hepatocarcinogenesis involves large molecular events including genetic and epigenetic changes, which accumulate through progression (Hui and Makuuchi, 1999;Zimmermann et al, 1997). The genetic deviation encompasses DNA rearrangements associated with viral genome integration (Zondervan et al, 2000), point mutations (Ogata et al, 1991;Shimizu et al, 1999;de La Coste et al, 1998), loss of heterozygosity (Teeguarden et al, 2000;Kondo et al, 2000), chromosomal amplifications (Kawate et al, 1999), changes in methylation (Kondo et al, 2000;Shen et al, 1998), translocations (Keck et al, 1999), and gain or loss of imprinting (de Souza et al, 1997;Schwienbacher et al, 2000). These changes could occur in a variety of cellular genes leading to escape from normal cellular and environmental controls.…”
Section: Introductionmentioning
confidence: 99%